Biology and Management of Spanish Needles (Bidens spp.) in Ornamental Crop Production - Yuvraj Khamare; Stephen Christoper Marble; Shawn T. Steed; Nathan S. Boyd (EDIS)
All eight species of Bidens in Florida are commonly referred to as Spanish needles or beggar-ticks. This document focuses on Bidens alba and B. pilosa, which are common weeds in container nurseries and landscapes in Florida. This 6-page EDIS publication, written by Yuvraj Khamare, Chris Marble, Shawn Steed, and Nathan Boyd and published by the UF/IFAS Environmental Horticulture Department, is designed for landowners, gardeners, horticulturalists, and consumers hoping to learn more about Spanish needle classification and management. http://edis.ifas.ufl.edu/ep572